Politisch unwürdig? Entschädigung von Kommunisten für nationalsozialistische Gewaltmaßnahmen Bundesdeutsche Gesetzgebung und Rechtsprechung der 50er Jahre - Bertheau, Camilla; Bertheau, Camilla (Juristische Zeitgeschichte / Abteilung 5, 2016)
What was the impact of the general political situation - that is, the Cold War - on the compensation of political victims of Nazi persecution, especially communists? This study examines legislative processes and jurisprudence and their reciprocal effects during the 1950s in West Germany, with a focus on juridical practice in West Berlin.